Evolution of Biochar Structure and Its Impact on Volatile Adsorption and Reforming during Char-Recycled Pyrolysis - Liping Du; Hengda Han; Aishu Li; Qiangqiang Ren; Song Hu; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Kai Xu; Jun Xiang (Energy Material Advances)
Bioenergy is considered a promising alternative due to its abundant resources and neutral property in CO2 circulation. Renewable bio-waste can be transformed into valuable energy and chemicals through thermal conversion technologies, aiding in the decarbonization of current industrial activities. The elimination of heavy components in volatiles produced by biomass pyrolysis through catalytic reforming is supposed to be an effective approach to enhance the quality of biofuel. As an environmentally benign carbon material, biochar features porous structures, abundant groups, and active radicals, contributing to its outstanding adsorptive capacity and catalytic activity. Char, serving as both adsorbents and catalysts, facilitates the adaptive conversion of pyrolysis products, and its physicochemical properties may have a considerable impact on the process of volatile adsorption and reforming. This review expounds on the recent advancements in the dynamic evolution of pores, active functional groups (AFGs), and persistent free radicals (PFRs) under different pyrolysis conditions. The diffusion of volatiles along pore channels and adsorption on active sites are markedly influenced by the spatial effects from sieving pores and electrostatic interactions among surface groups. The AFGs and PFRs could interactively engage in the catalytic reforming of volatiles by mediating electron transfer and inducing chain reactions. This paper may offer insights into the regulation of biochar properties and the migration of organic pollutants during biomass thermochemical conversion.